O que seria uma tese barthesiana? / What would be a barthesian thesis? - Coustille, Charles (Revista Polis e Psique, 2017)
Resumo A partir de textos inéditos de Roland Barthes (principalmente a dissertação sobre Ésquilo, os numerosos trabalhos doutorais inacabados e as anotações para o seminário sobre “Os problemas da tese e da pesquisa”), definimos as características de uma tese barthesiana: 1) ela não tem necessariamente um tema, seu objetivo é fabricar um objeto; 2) ela abandona seu método durante o percurso; 3) ela é desgraciosa, mas procura mesmo assim seduzir; 4) é uma maneira específica de orientar o desejo. Palavras-chave: Tese; Barthes; Escrita. Abstract From several unpublished texts (mainly the dissertation about Ésquilo, the numerous unfinished doctorals works and the notes for the seminary on "The problems of the thesis and research"), we defined the characteristics of a barthesian thesis: 1) it doesn’t necessarily have a theme, it’s objective is to fabricate an object; 2) it abandons it’s method during the course; 3) it is ungraceful, but even so seeks to seduce; 4) it is a specific way to orient the desire. Key words: Thesis; Barthes; Writing.